“Tudo é trabalho”: representações sociais de gestores de logística de transportes sobre o trabalho intensificado - Tavares, Ariane Serpeloni (Universidade Federal de São Carlos, 2019)
In this thesis we present the results and analyzes of a qualitative approach research, which general objective was to understand the social representations of logistics transport managers about their work. In order to understand this particular type of work-worker relationship, we used the concept of intensified work to characterize the relations and working conditions typical of this sector, the Social Representations Theory (SRT), in its sociological and procedural approach to identify how the subjects interpret their experiences and the Psychodynamic of Work to comprehend the subjective relation with work and it’s repercussion on Social Representation’s production, among other concepts. For that, we conducted semi-structured interviews with ten managers or coordinators who worked in the transportation sector of large private companies and who had experienced intensified working conditions in their professional trajectories. The intensified work demands a high physical and/or mental effort of those who work and, in the studied case, comprised the execution of activities at high pace, long journeys, extension of this beyond the formal working environment and constant use of communication devices, which demanded the permanent availability of managers to work. The main results indicated that the managers identified that the working conditions that they experienced were much more intense compared to those of their colleagues and their families and led to difficulties in reconciling private life with the demands of work, the dilution of the barriers between work and non-work and health impacts. On the other hand, managers also indicated that they were satisfied with the pace of work as well as the financial and career benefits stemming from the acceptance of intensified working conditions. We identified the presence of defensive strategies adopted by managers to deal with or alleviate suffering from work overload, as well as other elements that generated well-being at work. The explanations given by the managers for the occurrence of the intensified work involved: a) personal factors (anxiety, need of power, custom, lack of maturity); b) professional factors (need to grow professionally, inexperience); c) factors related to the company and the type of operation (department of work, lack of structure and team, demand for results, meritocratic culture, uninterrupted operations, off-hours drives, restructuring and leadership culture); d) factors such as the naturalization of intensified working conditions in the logistics sector and the need to maintain employment. Considering that the contents present in the transubjective sphere form the background for the construction of social representations, we identified that managers' RSs were anchored in managerial ideology, which naturalizes this way of working: to be profitable, to be available, reach results, dedicate themselves to the maximum. In addition, the subjective relation with the work was pointed out as relevant in the construction of these SRs. In considering that social representations are not only configured by the social context, but also shape it, we conclude that the managers' representations about the intensified work provide elements for the construction of the representations of other social groups, revealing the ambivalent character of the managerial position: victims and intensified labor agents.
“All is work”: social representations of logistics transport managers about intensified work
Keywords: Trabalho intensificado; Intensificação do Trabalho; Gestores; Logística; Trabalho imaterial; Ideologia gerencial; Psicologia social do trabalho; Representações sociais; Intensified work; Work intensification; Managers; Logistics; Immaterial work; Management ideology; Social psychology of work; Social representations; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL::FATORES HUMANOS NO TRABALHO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL